Factors Influencing the Decision to Purchase Cancer Insurance in Peru (2022) - Zela Dominguez, Jhon Arturo (2023)
The decision to purchase a good or service is influenced by environmental factors such as legal, economic, and political factors. This study examines the impact of these factors on the purchase of cancer insurance in the Peruvian market during the COVID-19 pandemic, using a review and comparison of different authors’ positions. Regarding the legal factor, Peru has approved the National Cancer Act and its regulations, which aim to improve services for cancer patients. However, there is a delay in the development of procedures to implement this law. Economically, various indicators predict positive growth projections for Peru in coming months, which bodes well for insurance supply and demand. Politically, the Peruvian government has faced several crises in recent years due to corruption, social conflicts, and an inadequate response to international events affecting the country, including the consequences of the war between Ukraine and Russia and the COVID-19 crisis. In this sense, there is a relationship between legal, political, and economic factors and the consumer’s decision to purchase cancer insurance, as recurrent crises could influence consumer’s decision to purchase insurance or prioritize other expenses in their consumer basket.